Budaya Patriarki dan Fenomena Fatherless - Panjaitan, Klara Septari; Damaiyanti, Varinia Pura (Multikultural: Jurnal Ilmu Sosial, 2025)
The phenomenon of fatherless has become a challenge in modern families, especially when the father's role is limited by patriarchal values that emphasize only economic functions. This study aims to explore the experiences of millennial Batak Simalungun fathers in carrying out parenting roles, particularly in the context of the Gereja Kristen Protestan Simalungun (GKPS) Banjarmasin. This research uses a qualitative approach with a descriptive phenomenological method. Data were collected through in-depth interviews, observation, and documentation with eight informants, including six fathers and two mothers. The results show that most fathers still view their role as breadwinners, while emotional closeness with children is considered the mother’s responsibility. However, there is a growing awareness among fathers to become emotionally involved, although this is still limited to simple actions and not yet consistent. Cultural values, childhood experiences, and social pressure are the main barriers to their involvement. This study emphasizes the importance of support from both families and social institutions to encourage a more equal and emotionally present fathering role.